Pengaruh Employee Engagement Terhadap Kinerja Karyawan pada PT MK Semarang: Hari Sucahyowati*, Andi Hendrawan - Hari Sucahyowati; Andi Hendrawan (Nama Jurnal Akmi, 2020)
ABSTRACT Employee engagement is a part of human resource studies. Employee engagement issues are a matter of concern because the impact of bad Employee engagement will result in employee performance being disrupted, even in various studies showing a significant relationship between Employee engagement and employee performance. This study aims to prove the impact of Employee engagement on the performance of employees of PT. MK is a company engaged in land and land transportation, export and import of goods. This study uses an exploratory analysis approach, which is the analysis used to analyze the relationship between the characteristics of respondents and the assessment of PT MK employees with employee involvement and employee performance. Approach. qualitative is done through observation and survey data collection. The influence of Employee engagement on the performance of Karywan PT. MK is very significant with a sig = 0.00. This means that there is an influence of Employee engagement on the performance of Karywan PT. MK . Semarang.